2015
DOI: 10.1124/jpet.114.222281
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Anticancer Drug Hydroxytriolein Inhibits Lung Cancer Cell Proliferation via a Protein Kinase Cα– and Extracellular Signal-Regulated Kinase 1/2–Dependent Mechanism

Abstract: Membrane lipid therapy is a novel approach to rationally design or discover therapeutic molecules that target membrane lipids. This strategy has been used to design synthetic fatty acid analogs that are currently under study in clinical trials for the treatment of cancer. In this context, and with the aim of controlling tumor cell growth, we have designed and synthesized a hydroxylated analog of triolein, hydroxytriolein (HTO). Both triolein and HTO regulate the biophysical properties of model membranes, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 50 publications
(65 reference statements)
2
20
0
Order By: Relevance
“…Exposing TNBC cells to HTO or TO (prepared as described previously [30]) reduced the number of viable cells in culture in a dose- and time-dependent manner. After 48 h, HTO more strongly affected BT-549 and Hs-5748T cells than TO (IC 50 59.2 ± 4.4 μM and 297 ± 73 μM for HTO; 146.6 ± 5 μM vs 412.5 ± 78 μM for TO, respectively: Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposing TNBC cells to HTO or TO (prepared as described previously [30]) reduced the number of viable cells in culture in a dose- and time-dependent manner. After 48 h, HTO more strongly affected BT-549 and Hs-5748T cells than TO (IC 50 59.2 ± 4.4 μM and 297 ± 73 μM for HTO; 146.6 ± 5 μM vs 412.5 ± 78 μM for TO, respectively: Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that a more stable TO analogue, hydroxytriolein (HTO), has a stronger antitumor efficacy than TO against non-small cell lung cancer (NSCLC). HTO is a 2-hydroxy fatty-acyl TO derivative that regulates membrane lipid structure, favoring the membrane translocation and activation of PKC and ERK, as well as the production of reactive oxygen species (ROS) and macroautophagy specifically in cancer but not in normal cells [30]. Here, we have used different human TNBC cell lines to evaluate the antitumor potential of HTO.…”
Section: Introductionmentioning
confidence: 99%
“…in terms of the glycerol backbone and three fatty acids. These molecules are good candidates for treating APBD and other conditions through membrane lipid therapy, particularly because they modulate the composition and structure of cell membranes, and because they are more stable than nonhydroxylated triacylglycerols (36). This therapeutic approach involves the regulation of the membrane lipid structure, as has formerly been considered to treat other CNS conditions like Alzheimer's disease or gliomas (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…This metabolism could reduce the bioavailability of TH and its therapeutic effects in patients. In order to overcome this problem, we designed a more stable hydroxylated TH analog (TGM0), a modification that offers some protection from triacylglycerol metabolism by lipases (36). TGM0 significantly increased GBE1Y329S activity in PBMC cells from APBD patients homozygous for that mutation and TGM5 also enhanced GBE1Y329S activity in vitro and ex vivo (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Altering this membrane lipid switch (i.e., changing the membrane lipid composition) may affect the localization and activity of proteins that promote proliferation, such as the farnesylated small GTPase Ras [251,252], and it also regulates membrane anchoring of tumor suppressors like PKC. Certain synthetic lipids like 2OHOA [88] and hydroxytriolein [249,253] alter the membrane's composition, reversing cancer cell proliferation and preventing the uncontrolled growth of cancer cells by relocating Ras to the cytosol [21], FoxO1 to the nucleus, PKC to the plasma membrane [21,98,245], or PKC to the cytosol through hydroxytriolein activity [253]. These alterations attenuate cancer cell proliferation, and induce differentiation, ER stress and ERK-dependent autophagic cell death.…”
Section: Protein-lipid Interactions and Cell Switchesmentioning
confidence: 99%